Application of amino‐based chitosan cyclodextrin derivatives for the extraction of catechins in green tea with high‐performance liquid chromatography. Issue 16 (20th June 2019) - Dai, Yunliang; Row, Kyung Ho
Abstract: Chitosan derivatives have been studied widely, but poor solubility in water restricts their applications. In this study, four types of amine‐based chitosan derivatives were prepared and modified further with beta‐cyclodextrin. The sequential microextraction of catechins ((+)‐catechin and (−)‐epigallocatechin gallate) from green tea powder by an optimized solid‐phase extraction method using these four derivatives was investigated. The optimal conditions for the extraction of catechins were 60°C for a 40 min extraction period. The purity and amount of each catechin were determined by high‐performance liquid chromatography. The different amines strengthened the extraction capacity of chitosan. Among the four types of amines, ethylene diamine grafted chitosan beta‐cyclodextrin had the highest extraction capacity to catechins. Therefore, this material was used in the extraction assay, and the standard curves of (+)‐catechin and (−)‐epigallocatechin gallate were linear over the concentration range, 0.25–500 µg/mL, after assaying five data points in duplicate. Solid‐phase extraction with the amino‐based chitosan beta‐cyclodextrin system is a new application of chitosan, which has potential applications in the extraction of bioactive compounds from plant materials or the removal of different impurities from specific extracts.